CFTR modulator therapy with lumacaftor/ivacaftor alters plasma concentrations of lipid-soluble vitamins A and E in patients with cystic fibrosis - Sommerburg, Olaf; Hämmerling, Susanne Hedwig; Schneider, Philipp; Okun, Jürgen G.; Langhans, Claus-Dieter; Leutz-Schmidt, Patricia; Wielpütz, Mark Oliver; Siems, Werner; Gräber, Simon Y.; Mall, Marcus A.; Stahl, Mirjam (Antioxidants, 2021)
Rationale: Cystic fibrosis (CF), caused by mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) gene, leads to impaired pancreatic function and therefore reduced intestinal absorption of lipids and fat-soluble vitamins especially in patients with CF developing pancreatic insufficiency (PI). Previous studies showed that CFTR modulator therapy with lumacaftor-ivacaftor (LUM/IVA) in Phe508del-homozygous patients with CF results in improvement of pulmonary disease and thriving. However, the effects of LUM/IVA on plasma concentration of the lipid soluble vitamins A and E remain unknown. Objectives: To investigate the course of plasma vitamin A and E in patients with CF under LUM/IVA therapy. Methods: Data from annual follow-up examinations of patients with CF were obtained to assess clinical outcomes including pulmonary function status, body mass index (BMI), and clinical chemistry as well as fat-soluble vitamins in Phe508del-homozygous CF patients before initiation and during LUM/IVA therapy. Results: Patients with CF receiving LUM/IVA improved substantially, including improvement in pulmonary inflammation, associated with a decrease in blood immunoglobulin G (IgG) from 9.4 to 8.2 g/L after two years (p < 0.001). During the same time, plasma vitamin A increased significantly from 1.2 to 1.6 µmol/L (p < 0.05), however, levels above the upper limit of normal were not detected in any of the patients. In contrast, plasma vitamin E as vitamin E/cholesterol ratio decreased moderately over the same time from 6.2 to 5.5 µmol/L (p < 0.01). Conclusions: CFTR modulator therapy with LUM/IVA alters concentrations of vitamins A and vitamin E in plasma. The increase of vitamin A must be monitored critically to avoid hypervitaminosis A in patients with CF.
Der Artikel erschien im Special Issue "Commemorative issue of antioxidants dedicated to Peter Eckl"
Gesehen am 07.05.2021